2014
DOI: 10.1177/1756287214537331
|View full text |Cite
|
Sign up to set email alerts
|

Experience in the use of collagenase clostridium histolyticum in the management of Peyronie’s disease: current data and future prospects

Abstract: Introduction: Peyronie's disease (PD) is a chronic wound-healing disorder characterized by formation of fibrous inelastic scarring of the tunica albuginea resulting in a variety of penile deformities. In most cases, PD is accompanied by a physical and psychological impact. Xiaflex ® is an injectable collagenase clostridium histolyticum (CCh) preparation consisting of a predetermined mixture of two distinct collagenases. Recently the US Food and Drug Administration (FDA) approved Xiaflex ® for the nonsurgical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Results suggest that prior treatment with CCH does not limit a patient's subsequent surgical straightening treatment options [32]; however, further well-designed studies are needed to confirm these initial observations. Studies assessing the long-term effects of CCH therapy [2,31], its use in patients with hourglass deformity, ventral curvature, calcified plaque or plaque located proximal to the base of the penis [31] and identifying predictors of optimal treatment success in subgroups of PD patients [27] would also be helpful.…”
Section: Current Status Of Cch In Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results suggest that prior treatment with CCH does not limit a patient's subsequent surgical straightening treatment options [32]; however, further well-designed studies are needed to confirm these initial observations. Studies assessing the long-term effects of CCH therapy [2,31], its use in patients with hourglass deformity, ventral curvature, calcified plaque or plaque located proximal to the base of the penis [31] and identifying predictors of optimal treatment success in subgroups of PD patients [27] would also be helpful.…”
Section: Current Status Of Cch In Patientsmentioning
confidence: 99%
“…Peyronie's disease (PD) is a fibrotic disorder characterized by penile plaque formation in the tunica albuginea, resulting in a variety of deformities, such as curvature, shortening, narrowing and hinge defect [1][2][3]. PD has a major impact on patients' sexual and psychological function [4], with almost half of the patients having relationship problems and clinically meaningful depression and 81 % of patients having emotional problems [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The disease has been shown to be prevalent, especially as men get older [1], and affects quality of life, principally through pain during erection, erectile dysfunction, loss of penetrative ability during intercourse, and associated psychological stress [2,3]. Despite the progress in understanding the pathophysiology of PD, there is currently a lack of efficacious medical therapies for PD, with surgery or collagenase injections [4] being the main treatment options. Although the surgical outcomes following penile straightening are well documented, surgery is invasive, costly, and frequently detrimental to penile size and erectile function [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the initial clinical trials, CCH was administered in doses reported in active biofactor units. The conversion factor for CCH is 10,000 active biofactor units equals 0.58 mg. 43 For convenience, all doses will be reported in milligrams.…”
Section: Collagenase Clostridium Histolyticummentioning
confidence: 99%